Efektivitas Pengawasan Badan Permusyawaratan Desa (BPD) Terhadap Pengelolaan Dana Desa (Desa Blahkiuh, Kecamatan Abiansemal, Kabupaten Badung) - I Komang Gerdion Ananda Junior; I Ketut Kasta Arya Wijaya; I Wayan Arthanaya (Jurnal Interpretasi Hukum, 2021)
Village funds are a form of assistance from the government as a means of support and means of encouraging development and empowerment of communities in the village, where the assistance is used to support community facilities in developing activities and potential in a village. The government budget given to the village is basically used to increase community development and empowerment. The purposes of this research are to examine the implementation of the supervision of the Village Consultative Body (BPD) on the management of village funds in Blahkiuh Village and the effectiveness of the supervision of the Village Consultative Body (BPD) on the management of village funds in Blahkiuh Village. This type of research used in this study is an empirical method, wtih socilogical approach and staturory approach. The results shows that Implementation of BPD supervision of village fund management in Blahkiuh Village, among others, is directed at realizing the desired future state by looking at the potential and needs of the Village. The effectiveness of BPD supervision on the management of village funds in Blahkiuh Village, among others, is not yet fully running, although the village budget is very important, such as construction / repair / maintenance activities for irrigation channels, roads, etc. This is influenced by low public participation, weak coordination between planning and budget execution